A Novel Successive Suturing Device for Laparoscopic Surgery. (August 2016) - Cho, Chang Nho; Cho, Sung Ho; Cho, Seong Yeon; Kim, Kwang Gi; Park, Sang Jae
Suturing is one of the more tiresome and difficult tasks during laparoscopic surgeries. To cope with this problem, we aimed to develop a novel successive suturing device. A novel needle holding and locking mechanism is proposed to transfer the needle between the upper and bottom jaws. The device is straightforward to use with intuitive 2-trigger control, and it can perform successive suturing without the need of reload between stiches. Also, it is compact enough to be inserted through a 12-mm trocar. The feasibility of the device is verified through in vitro and in vivo experiments. It was found that the developed device was able to successfully close the wounds without any leakage. The developed successive suturing device offers an easy way of performing suture, and it will greatly help surgeons during laparoscopic surgeries.